The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1111/j.1469-8137.1995.tb03065.x
|View full text |Cite
|
Sign up to set email alerts
|

A three‐dimensional representation of the relationship between penetration of u.v.‐B radiation and u.v.‐screening pigments in leaves of Brassica napus

Abstract: SUMMARYA three-dimensional (3-D) representation of the penetration of u.v.-B (280-320 nm) radiation using fibre-optic microprobes, and of the spectrophotometric analysis of u.v.-screening pigments in leaves of Bras.ii.ca napus L. cv. Ceres is presented. In this way the results from radiation measurements were directly related to the distribution of u.v.-screening pigments. Brassica napus was grown in a greenhouse chamber with a photon flux density of 740 /imo\ m"^ s"^ photosynthetically active radiation (400-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 23 publications
7
38
0
4
Order By: Relevance
“…Using Wbre-optic microprobes, it was shown that UV-B radiation was capable to reach mesophyll in B. napus leaves and to enhance Xavonoids and phenolic compounds mostly in the epidermis, but also in the internal layers (Alenius et al 1995). Despite no data are presently available on the penetration of UV-B radiation in tomato fruits, our data indicate that most Xavonoid genes are aVected by UV-B depletion in the Xesh of both genotypes, suggesting that UV-B has a direct or indirect role in modulating gene expression in Xesh.…”
Section: Discussionmentioning
confidence: 99%
“…Using Wbre-optic microprobes, it was shown that UV-B radiation was capable to reach mesophyll in B. napus leaves and to enhance Xavonoids and phenolic compounds mostly in the epidermis, but also in the internal layers (Alenius et al 1995). Despite no data are presently available on the penetration of UV-B radiation in tomato fruits, our data indicate that most Xavonoid genes are aVected by UV-B depletion in the Xesh of both genotypes, suggesting that UV-B has a direct or indirect role in modulating gene expression in Xesh.…”
Section: Discussionmentioning
confidence: 99%
“…Isso pode ser explicado, principalmente no caso de flavonóides e fenilpropanóides correlatos, pela proteção contra a foto-destruição proporcionada por estes metabólitos ao absorver e/ou dissipar a energia solar, dificultando assim a danificação dos tecidos mais internos pela radiação UV-B 101,[108][109][110] .…”
Section: Radiação Ultravioletaunclassified
“…Leaves contain water-soluble phenolic pigments, such as flavonoids, which strongly absorb UV-B radiation whilst not absorbing photosynthetically active radiation. These UV-B absorbing pigments are present throughout the leaf, but accumulate in adaxial epidermal cells [3][4] . UV-B radiation stimulates the expression of the genes encoding phenylalanine ammonia-lyase (PAL), the first stage of the phenylpropanoid pathway, and chalcone synthase (CHS), the key stage that commits the pathway to flavonoid synthesis (for reviews see Bornman and Teramura 5 , Beggs and Wellmann 6 , Jenkins et al 7 ).…”
Section: Introductionmentioning
confidence: 99%